PENDAMPINGAN MEMPEROLEH SERTIFIKAT HALAL - Marselina, Marselina; Joko Prasetyo, Tri; Ciptawaty, Ukhti (Faculty of Economics and Business Lampung University, 2023)
With the end of the Covid-19 pandemic, it is hoped that the MSME sector will recover. Halal products are very important in today's society. Simultaneously, the Indonesian Ministry of Religion's Halal Product Assurance Organizing Agency (BPJPH) issued a regulation that all MSME products must be halal-certified by 2024. Halal certification is very important to ensure consumers feel safe and that what they buy does not violate Islamic rules. Knowledge and understanding of SMEs regarding halal certification and business registration numbers (NIB) are still relatively minimal, as indicated by the low number of SMEs with halal certification. In order to increase the number of MSME businesses, this service activity aimed at 60 MSMEs around the University of Lampung area aims to facilitate direct socialization and halal certification of MSMEs. The current halal certification authorization process uses an online system which is preceded by an understanding of halal and socialization of NIB, making it easier and helping SMEs in obtaining halal certification. From this activity, it is hoped that SMEs in Lampung Province can grow better and faster. This service activity is in collaboration with the Halal Center for Muslim Scholars of the Ministry of Religion and the women's organization Women's Empowerment of UMKM (PPUMI) Lampung.